From Wilderness to Timberland to Vacationland to Ecosystem: Maine’s Forests, 1820–2020 - Irland, Lloyd (Maine Policy Review, 2020)
The 200 years since Maine statehood span a series of changing metaphors used by people to understand the forest and its values: the forest as wilderness, as timberland, as vacationland, and as ecosystem. These metaphors have succeeded each other over time, but broadly speaking, they all persist to one degree or another. These ways of viewing and using the forest can conflict or can come to uneasy truces, but new developments can revive the tensions. Public policy is always well behind the shifting needs as timberland comes to be seen as vacationland and vacationland as ecosystem. Further, conflicts between different visitors to vacationland can be among the most difficult to solve. As Maine moves into its third century, the momentum of forest regrowth has shifted into reverse gear: for the first time in a century or more, total forest area is beginning to shrink.
Keywords: Maine rivers; paper mills; wildlife; recreation; carbon sink; land booms; wildland urban interface